Degradation problem in silver nanowire transparent electrodes caused by ultraviolet exposure. (9th March 2020) - Lin, Chiao-Chi; Lin, Dong-Xuan; Lin, Shih-He
Abstract: Silver nanowire (AgNW) transparent electrode inevitably encounters ultraviolet (UV) irradiation from the environment, leading to stability and durability problems when in operation. Since UVA is the most abundant UV band and highly penetrating to AgNW related optoelectrical devices, it is crucial to understand the UVA damage caused to AgNWs. In this study, transparent electrodes composed of pristine AgNWs and glass substrates were manufactured with optimized processing parameters, and then used as model samples for aging tests. UVA exposure was conducted at elevated temperatures including 45 °C, 60 °C and 75 °C at 12 ± 5.5% relative humidity (RH) conditions. Comparative aging tests using conditions of damp heat (85 °C/85% RH) and 105 °C without UV (dark conditions) were also conducted. The relationship between optoelectrical property degradation, morphological changes and photo-corrosion was discussed. Under UVA exposure, the sheet resistance of electrodes increased gradually in an induction period before an abrupt change occurred. A nominal sheet resistance value of 200 Ω/sq was considered as a predestined failure of electrical property. It took 16, 24 and 60 h for UVA exposure at 75 °C, 60 °C and 45 °C, respectively, and 288 h by damp heat aging to degrade to the same status of predestined failure. Aging results of dark conditions indicated no degradation effect on AgNWs for 126 d aging. Moisture caused a different mechanism in damaging the capping agents on AgNWs. Nanocubes of silver chloride and sodium chloride were prone to precipitate at higher aging temperature such as 75 °C with UVA exposure. Sulfidation accounted for deterioration of optical transmittance, and occurred significantly at 45 °C with UVA irradiation and under damp heat conditions. The synergistic aging effect of UVA irradiance at elevated temperature on AgNW degradation has been unambiguously demonstrated. The results of this study provide guidelines for the design of optoelectronic devices when utilizing AgNW transparent electrodes.